2010
DOI: 10.1063/1.3462398
|View full text |Cite
|
Sign up to set email alerts
|

Intergrain connectivity of MgB2 ceramics studied by impedance analysis

Abstract: First, by using of the conventional Rowell analysis, we demonstrated that the addition of nano BN particles can effectively eliminate MgO and pores in MgB 2 resulting in a very high density and good connectivity of BN-doped MgB2. Then, another method-low-frequency dielectric impedance analysis-was introduced to characterize the properties of the grain boundaries of MgB 2 . A comparative impedance study was performed in the frequency range from 100 Hz to 100 MHz on pure and nano BN-doped MgB 2 . The study revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…4. It confirms the spread of relaxation time [26], i.e., the existence of a temperature-dependent electrical relaxation phenomenon in nanocrystalline Li 2 TiO 3 .…”
Section: Cis Studysupporting
confidence: 65%
“…4. It confirms the spread of relaxation time [26], i.e., the existence of a temperature-dependent electrical relaxation phenomenon in nanocrystalline Li 2 TiO 3 .…”
Section: Cis Studysupporting
confidence: 65%
“…The amount of H and OH introduced into MgB2 samples with h-BN doping increases as the particle size decreases due to increasing surface/volume ratio. This may play an important role in the mechanism mentioned above and we suggest that it may provide explanation for the controversy in the literature upon BN doping [26,27]. This discussion is further supported by the fact that when we added 5 % h-BN (not supplemented) which is half of [26] and [27] transport critical transition was broader then 5 K which was our reason to decrease h-BN addition to 3 %.…”
Section: Resultssupporting
confidence: 52%
“…This may play an important role in the mechanism mentioned above and we suggest that it may provide explanation for the controversy in the literature upon BN doping [26,27]. This discussion is further supported by the fact that when we added 5 % h-BN (not supplemented) which is half of [26] and [27] transport critical transition was broader then 5 K which was our reason to decrease h-BN addition to 3 %. In the study of Wang et al [27], it has been concluded that 10 % h-BN doping increases the connectivity and improves the high field Jc properties of the MgB2 in contrary to the findings reported in the study of Kovak et al [26].…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…2 However, when we extend the study of resistivity to polycrystalline samples, the Rowell relation fails to quantitatively describe the connectivity for this system. 3 Yamamoto et al 4 suggested an improved model by using the packing factor to evaluate the connectivity in polycrystalline MgB 2 based on a percolation method. On the other hand, since in the superconducting state, the superconducting transition broadening, as found in resistivity measurements in the presence of magnetic fields, contains important information related to the basic vortex-pinning mechanisms governing the critical current density.…”
Section: Introductionmentioning
confidence: 99%